Motor Evoked Potentials Correlate With Magnetic Resonance Imaging and Early Recovery After Acute Spinal Cord Injury. Issue 6 (June 2018) - Dhall, Sanjay S; Haefeli, Jenny; Talbott, Jason F; Ferguson, Adam R; Readdy, William J; Bresnahan, Jacqueline C; Beattie, Michael S; Pan, Jonathan Z; Manley, Geoffrey T; Whetstone, William D
Abstract: BACKGROUND : While the utilization of neurophysiologic intraoperative monitoring with motor evoked potentials (MEPs) has become widespread in surgery for traumatic spine fractures and spinal cord injury (SCI) clinical validation of its diagnostic and therapeutic benefit has been limited. OBJECTIVE : To describe the use of intraoperative MEP at a large level I trauma center and assess the prognostic capability of this technology. METHODS : The SCI REDCap database at our institution, a level I trauma center, was queried for acute cervical SCI patients who underwent surgery with intraoperative monitoring between 2005 and 2011, yielding 32 patients. Of these, 23 patients had severe SCI (association impairment scale [AIS] A, B, C). We assessed preoperative and postoperative SCI severity (AIS grade) surgical data, use of steroids, and early magnetic resonance imaging (MRI) findings (preoperatively in 27 patients) including axial T2 MRI grade (Brain and Spinal Injury Center score). RESULTS : The presence of MEPs significantly predicted AIS at discharge ( P < .001). In the group of severe SCI (ie, AIS A, B, C) patients with elicitable MEPs, AIS improved by an average of 1.5 grades (median = 1) as compared to the patients without elicitable MEP who improved on average 0.5 grades (median = 0, P < .05). In addition, axial MRI grade significantly correlated with MEP status. Patients without MEPs had a significantly higher axial MRI grade in comparison to the patients with MEPs ( P < .001). CONCLUSION : In patients with severe SCI, MEPs predicted neurological improvement and correlated with axial MRI grade. These significant findings warrant future prospective studies of MEPs as a prognostic tool in SCI.